Aspects Regarding Ethics and Integrity in Romanian Scientific Research - Nicolae Lupu; Dragos Bigu (Amfiteatru Economic Journal, 2022)
In order to genuinely perform its function in society, scientific research in general and social research in particular must comply with ethical standards, which guarantee that the research results are correct, in accordance with the needs of society, do not harm research subjects and the community as a whole, and do not violate the rights of any research participant. Integrity codes and research ethics committees play a central role in ensuring the compliance of scientific practice with ethical standards. In order to highlight the degree of compliance of research activities with ethical norms, as well as specific problems, we will resort to the method of content analysis of complaints regarding potential violations of ethical norms, reports and decisions from recent years of the National Council of Ethics of Scientific Research, Technology Development and Innovation, as well as the National Council for Attesting University Titles, Diplomas and Certificates, attached to the relevant ministries in Romania.
Keywords: I23; O32; O34; 330; ethics; scientific research; content analysis; scientific research; content analysis; misconduct; sanction; integrity code.